Securing online quizzes and test on iTa’LeEM - Abdul Aziz, Normaziah; Mansor, Hafizah; Abdul Kadir, Andi Fitriah; Amir Hussin, Amir 'Aatieff (Centre for Professional Development (CPD), International Islamic University Malaysia., 2020)
IIUM’s Interactive Teaching and Learning Environment System (iTa'LeEM) comes with many great security features to make conducting online assessment more secured. The assessment can be an online quiz or test within a specific time allocated. The built-in quiz functions allow customisation that can help to increase security and integrity when conducting online assessment such as quizzes and tests. These features can be found mostly by expanding the Extra restriction on attempts when setting up your assessment.